Digital Teaching, Inclusion and Students’ Needs: Student Perspectives on Participation and Access in Higher Education - Wilkens, Leevke (Social Inclusion, 2021)
In this article we discuss the contribution of digitalisation for equal participation in higher education. Its potential is often postulated, but accessibility is seldom examined in this context. Despite the challenges and difficulties created in the summer term of 2020, this semester has provided a great opportunity to collect data on digital teaching, as face‐to‐face teaching needed to be transformed into digital teaching. Based on two surveys conducted in the summer of 2020, current practices and students’ needs regarding accessibility are outlined. Despite the circumstances, it can be derived from the surveys that digital teaching generally provides a variety of advantages for students with disabilities, although some tools and platforms remain not fully accessible to them. Additionally, the results indicate that not only students with sensory impairments benefit from the principles of the Web Content Accessibility Guidelines (2018). In particular, the principles ‘operable’ and ‘understandable’ are beneficial for students with mental health difficulties. Regarding the assessment of accessibility features, the study shows that the perception of students with and without impairments is very similar.